The Essence Of The Needs Of Students In Islam - Zahra, Aqila; Tinambunan, Nur Asiah; Razali, Razali (Journal of Sustainable Education, 2025)
This study aims to understand the essence of students' needs from an Islamic perspective and how fulfilling these needs can support a holistic and balanced educational process. In Islamic education, students' needs encompass not only physical and intellectual aspects but also spiritual and ukhrawi (hereafter-related) dimensions, with the goal of shaping a whole and morally upright personality. Understanding these needs is essential to ensure that the learning process is meaningful and aligned with the students’ natural disposition (fitrah). The research method used is qualitative with a descriptive approach. Data were obtained through library research by reviewing various secondary sources such as books, academic journals, articles, and other relevant documents. The results show that students' needs in Islam include spiritual, intellectual, emotional, and physical needs, which must be fulfilled in a balanced manner. Islamic education emphasizes the importance of comprehensive development of students’ potential in order to produce individuals who are monotheistic, knowledgeable, and virtuous. This has significant implications for teachers in developing contextual and value-based learning strategies.